PANDEMI COVID-19 DAN IMPLIKASINYA TERHADAP PEMBELAJARAN DI SEKOLAH - Maria Helmina Nara; Rosalia Erina Jehari (Jurnal Literasi Pendidikan Dasar (JLPD), 2022)
Indonesia was affected by the Covid-19 pandemic. The pandemic has had a negative impact on people's lives, including the education system, starting from a primary institutions to the colleges because educational activities could not be carried out face-to-face directly. Learning activities experienced a setback due to the pandemic. The impact was experience both in the economic field where people were happier online shopping ranging from clothes shopping to food. Likewise learning activities teaching was carried out from home. Work was also done from home with a goal reduce the spread of this deadly virus. The danger of this corona virus has paralyzed many community activities, in all activities, hinder teaching and learning activities in schools as well.